Spectrophotometric Determination of Palladium(II) with 3-Phenylazohydroxylamine - Swami, V.K.; Mathur, S.P. (Asian Journal of Chemistry, 2010)
3-Phenylazohydroxylamine has been suggested as photometric reagent for determination of palladium(II). The complex shows constant absorbance to the pH range of 5.0 at 425 mm and Beer's law is obeyed upto 8.5 ppm. The sensitivity of the reagent is 0.0054 g/cm–2 and molar absorptivity 5.69 x 104 1 mol–1 cm–1 at 425 mm.